SELF-INJURIOUS BEHAVIOR IN EDUCATION AND IMPLEMENTATIONS FOR EDUCATORS - Garro, Nicholas Charles (Acta Scientiae et Intellectus, 2024)
The following paper reviews and discusses Self-Injurious Behavior (SIB) and Non-Suicidal Self-Injury (NSSI) in the educational setting. The main focus of this text is SIB among youth who have significant cognitive and intellectual disables. However, NSSI could not be dismissed due to a large majority of adolescents who engage in non-suicidal self-injury. Furthermore, the text will cover signs, symptoms, diagnosis, treatment, and how to hand self-injurious behavior in a school environment. A significant portion of this text will cover implementations for educators when working with a student who has severe development delays in the school setting.